(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Human Rights - the Theological Fringe of a Political Project The present article emphasizes the manner in which the human rights discourse is seen by Orthodox theologians. Generally, the Orthodox Church considers the respect for the rights and the dignity of the person a central goal of her missionary activity, and from this point of view she shares along with the human rights discourse a common task. Nevertheless, Orthodox theologians propose that concepts like dignity, freedom and fraternity should be interpreted from the ultimate scope of Christian revelation, which is preparing believers for the Kingdom of Heaven. Also, for the Christian man the accomplishment of all human rights should be regarded from the perspective of the right to holiness. In this way a return to the biblical context of the emergence of the human rights is stressed by some theologians. The interpretation of the human right in the light of what the Old Testament is revealing to us offers a good opportunity to a better understandig of what it means to be righteous, what is righteousness and what are human rights.